Towards quantification of protective antibody responses by passive transfer of the 1st WHO International Standard for Ebola virus antibody in a guinea pig model. Issue 2 (10th January 2020) - Dowall, Stuart D.; Kempster, Sarah; Findlay-Wilson, Stephen; Mattiuzzo, Giada; Graham, Victoria A.; Page, Mark; Hewson, Roger; Almond, Neil
Abstract: Ebola virus (EBOV) represents a major concern to global health due to the unpredictable nature of outbreaks. Infection with EBOV can cause a severe viral haemorrhagic fever with no licensed vaccine or treatment, restricting work with live EBOV to Containment/Biosafety Level 4 facilities. Whilst the magnitude of recent outbreaks has provided an impetus for vaccine and antiviral development, establishing the efficacy of candidate vaccine materials relies on EBOV challenge models and advanced human trials should outbreaks occur and where logistics and funding allow. To address these hurdles in vaccine development, we investigated whether a recently established serological reference standard, the 1st WHO International Standard for Ebola virus antibody, could be used to provide a quantifiable correlate of immune protection in vivo . Dilutions of the International Standard were inoculated into naïve guinea pigs 24 h before challenge with a lethal dose of Ebola virus. Only subjects receiving the highest dose of the International Standard exhibited evidence of delayed progression. Due to it being a WHO established reagent and available globally upon request, this standard allows for effective comparisons of data between laboratories and may prove valuable to select the candidate vaccines that are most likely to confer humoral immune protection ensuring the most promising candidates progress into efficacy studies.